PERAN KELEMBAGAAN PETANI TERHADAP EFISIENSI TEKNIS USAHATANI DI DESA KEDUNGPRIMPEN KECAMATAN KANOR - Intan Nur Hidayah; Moh. Yusuf Dawud; Noor Djohar (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2026)
Limited access to agricultural inputs and technical information is often a major obstacle in optimizing farmer productivity. Farmer institutions play a vital role in supporting farmers in managing their farms; efforts to increase efficiency through institutional strengthening are a pressing issue. The purpose of this study was to analyze the role of farmer institutions in the technical efficiency of rice cultivation in Kedungprimpen Village, Kanor District, Bojonegoro Regency. The study was conducted from December 2025 to January 2026 using a survey method involving 62 farmers selected by purposive sampling. The data were analyzed using the Cobb-Douglas production function SFA and MLE method. The results showed that the cultivated area and seed quantity had a positive and significant influence on rice production. Conversely, fertilizers, pesticides, labor, agricultural machinery, and HIPPA did not show a significant effect on production results. The technical inefficiency model found that farmer institutions and farmer education variables had a negative and significant effect, indicating that both play a major role in increasing technical efficiency. The average technical efficiency value of 0.895 indicates that rice cultivation in the study region is classified as efficient. Thus, farmer institutions play an important role in increasing technical efficiency by strengthening access to information, coordination, and collaboration among farmers.